Formulation, Characterization, and Antioxidant Properties of Chitosan Nanoparticles Containing Phenolic Compounds from Olive Pomace - Ilaria Fierri; Roberto Chignola; Chiara Stranieri; Edoardo Giuseppe Di Leo; Maria Bellumori; Sara Roncoletta; Alessandro Romeo; Federico Benetti; Anna Maria Fratta Pasini; Gianni Zoccatelli (Antioxidants)
Olive phenolic compounds like hydroxytyrosol (OH-Tyr), tyrosol (Tyr), and their precursors have different health-promoting properties, mainly based on their strong antioxidant capacity. However, their presence in extra-virgin olive oil (EVOO) is scarce since they are primarily contained in the by-products of oil production, such as olive pomace (OP). The aim of this work was to extract and encapsulate OP phenolic compounds into chitosan–tripolyphosphate nanoparticles (NPs) using an ionotropic gelation lyophilization approach to increase their resistance to environmental and chemical stress. NPs resulted in a monodisperse (PDI: 0.21) population of cationic NPs (ζ-potential: 33 mV, size: 229 nm) with an encapsulation efficiency (EE%), expressed as total phenolic content (TPC) and total OH-Tyr + Tyr content, of 64–65%. Mannitol and maltodextrin DE 19 (MD-19) were evaluated as lyoprotectants to counteract irreversible NP aggregation during lyophilization. The NP powder freeze dried using 0.7% of MD-19 showed the best performance, returning a monodispersed population of particles after rehydration. The antioxidant capacity of the obtained NPs was confirmed both in cell-free assays and in a THP-1 cell model of oxidative stress. This method represents a promising way to deliver health-promoting olive phenols for nutraceutical purposes and, hence, to valorize otherwise wasted by-products.